ANALISIS PELAKSANAAN ASESMEN DIAGNOSTIK DALAM MENGIDENTIFIKASI MINAT BELAJAR SISWA KELAS IV PADA PEMBELAJARAN IPAS DI SD 40/I BAJUBANG LAUT - Aminah, Siti Aminah; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of diagnostic assessments in identifying the learning interests of fourth-grade students in science education at SD 40/I Bajubang Laut. The study employed a descriptive qualitative approach, utilizing data collection techniques such as observation and in-depth interviews with the classroom teacher and six students selected through purposive sampling. The results indicate that students’ learning interests generally fall into the moderate category, accounting for 60%, with the dimensions of enjoyment and curiosity being relatively higher compared to the dimensions of attention and active engagement. The interviews revealed significant diversity in learning profiles, including active-enthusiastic students with low self-regulation, independent-inquisitive students with very high interest, and students with moderate interest who require more intensive scaffolding. The implementation of diagnostic assessments by teachers was found to remain informal and predominantly focused on the cognitive dimension, while non-cognitive diagnostic assessments to map interests and learning styles have not yet been formally and standardizedly implemented.